Taxonomic position of Pontonides sympathes De Ridder & Holthuis and species of the genus Veleronia Holthuis (Decapoda, Palaemonidae, Pontoniinae) with the description of a new genus - Marin, Ivan (Zootaxa, 2008)
The type specimens of Pontonides sympathes De Ridder & Holthuis, 1979, Veleronia serratifrons Holthuis, 1951, and V. laevifrons Holthuis, 1951 were re-examined. Pontonides sympathes is transferred to Veleronia Holthuis, 1951, based on morphological similarity with V. serratifrons, the type species of the genus. At the same time, a new genus, Pseudoveleronia gen. nov., is erected for Veleronia laevifrons. Detailed re-descriptions of all studied species as well as a key to the genera Pontonides Borradaile, 1917, Veleronia and Pseudoveleronia gen. nov. are given.